Riverine fishing methods with special reference to catfishes Aorichthys seenghala (Sykes) and Aorichthys aor (Ham.) - Seth, R N; Katiha, Pradeep K (Indian Journal of Fisheries, 2011)
The environmental stress on rivers has reduced lucrative carp and clupeid fisheries and shifted fishing pressure to other commercially important fishes, particularly Aorichthys seenghala (Sykes) and Aorichthys aor (Ham.), the two large sized catfishes. These contributed significantly in fish catches of middle stretches of Ganga River system. In existing milieu, the changed status of fisheries caused a drift in fishing practices, which required greater attention. The present paper studies scenario of fishing methods during 1991-‘99 with special reference to Aorichthys spp. The study revealed a gradual shift from low to lower energy gears. The period of operation of these gears has also been belated by couple of months over a year. The two gears, namely, Gopal and Ranga jal were most commonly used for fishing Aorichthys spp., therefore, studied in detail. The Ranga jal has come in operation very recently. It is described for the first time.